Prevalence of food allergens in different age groups in and around pollachi, coimbatore, Tamil nadu, South india - K.SIVANANDHAN,; NALINI SIVANANDHAN,; L.BANUPRIYA,; M.PALANISWAMY, (International Journal of Pharma and Bio Sciences, 2017)
This study is conducted to know the prevalence of food allergens among the 196 atopic patients (105 males and 91 females) who have visited Asthma Research Centre, Pollachi. These patients are divided into six groups namely, Group-A consists 2 to 5 years of age, Group-B is 6 to 10 years, Group-C is 11 to 20 years, Group-D is 21 to 30 years, Group-E is 31 to 50 years and Group-F is 51 years of age and above. Presence of food allergens is tested using the Euroline test kit. Analysis of the results show the main food allergens in various age groups like potato, crab, and peanut. Allergy to cow’s milk, egg, and milk powder are negligible. In group A and B, more males are affected, in group C and D males and females are equally affected, in group E more females are affected, and in group F again more males are affected. In Western countries, the main allergens are milk, egg, peanut, chicken, soya and fish. This results suggest that the allergens are vary place to place.